2013
DOI: 10.1038/bmt.2013.132
|View full text |Cite
|
Sign up to set email alerts
|

The impact of T-cell depletion techniques on the outcome after haploidentical hematopoietic SCT

Abstract: on behalf of Swiss Blood Stem Cell Transplantation Several T-cell depletion (TCD) techniques are used for haploidentical hematopoietic SCT (HSCT), but direct comparisons are rare. We therefore studied the effect of in vitro TCD with graft engineering (CD34 selection or CD3/CD19 depletion, 74%) or in vivo TCD using alemtuzumab (26%) on outcome, immune reconstitution and infections after haploidentical HSCT. We performed a retrospective multicenter analysis of 72 haploidentical HSCT in Switzerland. Sixty-seven p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 34 publications
(71 reference statements)
0
31
1
4
Order By: Relevance
“…Graft selection may affect lymphocyte ontogeny and delay immune reconstitution after transplant, as shown in previous studies. 16,17 Indeed, in allogeneic transplants, CD34+ selection delayed the CD4 T-lymphocyte reconstitution process, but the difference disappeared 8 months after transplantation, when compared with non-selected patients under similar conditions. 16 In addition, when comparing haploidentical hematopoietic stem cell transplant outcomes after ex vivo CD34+ selection or in vivo purging (alemtuzumab), the incidence of infections was similar, 17 indicating that both depletion methods are equally immunosuppressive.…”
Section: Resultsmentioning
confidence: 99%
“…Graft selection may affect lymphocyte ontogeny and delay immune reconstitution after transplant, as shown in previous studies. 16,17 Indeed, in allogeneic transplants, CD34+ selection delayed the CD4 T-lymphocyte reconstitution process, but the difference disappeared 8 months after transplantation, when compared with non-selected patients under similar conditions. 16 In addition, when comparing haploidentical hematopoietic stem cell transplant outcomes after ex vivo CD34+ selection or in vivo purging (alemtuzumab), the incidence of infections was similar, 17 indicating that both depletion methods are equally immunosuppressive.…”
Section: Resultsmentioning
confidence: 99%
“…3,6,7 In this study, however, the early rise in the infused CD3 1 CD19 1 T cells was rapidly followed by recovery of endogenous CD3 1 CD19 2 T cells compared with patients who underwent haplo-HSCT without T-cell add-back at concurrent points posttransplant (Amrolia et al 6 ; Figure 1B). At the time of T-cell infusion, CD3…”
Section: Effects Of the Infusion Of Ic9-t Cells On Total T-cell Engramentioning
confidence: 91%
“…Although extensive T-cell removal of the graft effectively prevents GvHD, the process also causes prolonged and profound posttransplant immunodeficiency for a year or more, 3,4 with compromised antiviral immunity. [5][6][7] As a consequence, infectious morbidity and mortality remain high and are a frequent cause of treatment failure. [8][9][10] Other groups and our own have shown that the posttransplant infusion of small numbers of donor T lymphocytes that have been depleted of recipient-reactive T cells can improve immune reconstitution and antiviral immunity.…”
Section: Introductionmentioning
confidence: 99%
“…There is no evidence indicating which protocol is better. 36 Ciurea et al 37 compared TCR and TCD haploidentical HSCT and found that TCR protocol had a fast immune recovery. This result is in accordance with our data, 7,38 suggesting that a rapid immune reconstitution may contribute to a superior outcome as reported by Ciurea et al 37 Interestingly, healthrelated quality of life in unmanipulated HBMT at our centre is comparable to that in patients receiving HLA-identical sibling allo-HSCT.…”
Section: Discussionmentioning
confidence: 99%